Cathode material with coating layer, preparation method of cathode material and lithium ion battery
By adopting a clad structure in the positive electrode material of lithium-ion batteries and lithium cobalt compounds containing Co and Al elements, the problem of difficult to take into account both the heat and gas production of the positive electrode material at high voltage is solved, and higher stability and safety are achieved.
Patent Information
- Application Number
- CN202510361862.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
The prior art is difficult to reduce heat and gas production between 4.3V and 5V in the positive electrode material of lithium-ion batteries at the same time, resulting in thermal runaway fire and explosion in the battery cell under high voltage conditions.
A positive electrode material with a cladding layer is used, and its core is LiαNixCoyAlzAmO2. The cladding layer contains Co elements and X elements. The mass ratio of X elements is 50% to 100%. Al elements are introduced into the cladding layer. Spinel type LiCoO2 is used as the main body of the cladding layer, and a specific content of LiaCo1-aCo2O4 and LibCo1-bO are combined.
By stabilizing the interface structure and reducing ohmic heat, low heat and gas production are achieved under high voltage, improving the stability of the positive electrode material and the safety of lithium-ion batteries.
Smart Images

Figure CN119890275A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a positive electrode material with a coating layer, a preparation method thereof and a lithium ion battery. Background Art
[0002] Nowadays, lithium-ion batteries are widely used in all walks of life as an environmentally friendly green energy source. High-rate tool electronic products have increasingly higher requirements for the safety characteristics of lithium-ion batteries under electrical abuse and high temperature conditions. Considering the actual application scenarios of rate-type batteries, it is required that the battery cells do not catch fire or explode during the process of constant current charging from open circuit voltage to cut-off voltage. Generally, the cut-off voltage exceeds the upper limit voltage of normal application. In order to meet customer needs, lithium-ion batteries continue to innovate in the design of battery cell structure, but the intrinsic safety improvement of each component of the battery cell is still the focus. Among them, the positive electrode material generates ohmic heat in accordance with Ohm's law from the open circuit voltage to the normal application voltage range (<4.3V) due to its intrinsic impedance, and almost no gas is produced; under high voltage conditions (for example, ≥4.3V), as the amount of lithium removal increases, the crystal structure becomes increasingly unstable, and lattice oxygen loss and Ni valence state increase are prone to occur, reacting with the electrolyte to produce a large amount of gas and heat, which in turn causes thermal runaway of the battery cell, fire and explosion.
[0003] Generally speaking, heat generation and gas generation complement each other. If heat accumulates too quickly, the metastable structure will become unstable, and the structure will decay or react with the electrolyte. If the gas generation increases suddenly and the reaction is violent, the heat generation will also increase sharply. Gas generation and heat generation are in a vicious cycle. Although the battery cell structure is designed to discharge and cut off the power in time, fire and explosion will still occur. Therefore, it is crucial to simultaneously reduce the heat generation and gas generation of the positive electrode material between 4.3V and 5V.
[0004] Unfortunately, in the prior art, for the positive electrode of lithium-ion batteries, the heat generation and gas generation of the positive electrode material between 4.3V and 5V cannot usually be taken into account at the same time. Usually, doping or coating with elements such as Al, Co, Zr, Mg, etc. in the bulk phase and surface of the positive electrode material can stabilize the bulk lattice or surface structure and improve its crystal structure stability at high voltage. However, not all coating elements or coating amounts can achieve the purpose of improvement. The reason is: for coating with inactive elements, the impedance of the material in the bulk will be significantly deteriorated, the heat generation will be greatly increased, the temperature of the battery cell will be increased, and the gas generation reaction will be promoted, and then thermal runaway; for coating with active elements, although the ohmic heat will be reduced, the surface reaction activity will be increased. Under high voltage, the structure is unstable, and structural decomposition and electrolyte side reactions are prone to occur, which greatly increases gas and heat generation.
[0005] Therefore, how to select the coating elements and amounts to balance the heat and gas production of the positive electrode material between 4.3V and 5V has become one of the problems that the industry urgently needs to solve. Summary of the invention
[0006] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a cathode material with a coating layer, a preparation method thereof, and a lithium-ion battery.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a cathode material with a coating layer, the cathode material with a coating layer includes a cathode core and a coating layer coated on the surface of the cathode core, and the chemical composition of the cathode core is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x + y + z + m = 1, wherein, A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba, and Ti;
[0009] The coating layer contains Co element and X element, and the mass ratio of X element to Co element in the coating layer is 50% - 100%; X is a metal element different from Co, and more than 50wt.% of X is Al element; the coating layer includes a lithium cobalt compound, and the lithium cobalt compound includes Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2, wherein, 0 < a < 1, 0 < b < 1, and the contents of Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2 in the total mass of the three (i.e., Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2) are 1wt.% - 15wt.%, 10wt.% - 25wt.%, and 65wt.% - 76wt.%, respectively, and the content of Li b Co 1-b O is greater than the content of Li a Co 1-a Co2O4;
[0010] Based on the total mass of the cathode core, the content of Co element in the coating layer is 1000ppm - 4000ppm.
[0011] In one embodiment, the mass ratio of the X element in the coating layer to the Co element in the coating layer is greater than or equal to 50% and less than 100%, and in this case, the contents of the two are different.
[0012] In another embodiment, the mass ratio of the X element in the coating layer to the Co element in the coating layer is 100%, that is, the contents of the two are the same.
[0013] Preferably, the mass fraction of the X element in the coating layer is smaller than that of the Co element in the coating layer.
[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] In one embodiment, X is 100 wt.% of Al element. Therefore, the coating layer contains Co element and Al element, and the mass ratio of the Al element in the coating layer to the Co element in the coating layer is 50% to 100%.
[0016] Preferably, the total mass of the Co element and the X element in the coating layer is ω1, and the total mass of the metal elements (excluding the lithium metal element) in the coating layer is ω2, then ω1 / ω2≥90%, preferably ≥95%. That is, the Co element and the X element in the coating layer account for more than 90% of the total mass ratio of the metal elements (excluding the lithium metal element) in the coating layer, and more preferably 95%.
[0017] In the present invention, if other metals and other trace metal doping are not considered, the Co element and the X element in the coating layer of the present invention can account for nearly 100% of the total metal elements (excluding lithium metal elements) in the coating layer.
[0018] Preferably, when X is 100% Al, the Co and Al elements in the coating layer account for more than 90% of the total mass ratio of the metal elements (excluding lithium metal elements) in the coating layer, and more preferably 95%. In the present invention, if other metals and other trace metal doping are not considered, the Co and Al elements in the coating layer of the present invention can account for nearly 100% of the total mass ratio of the metal elements (excluding lithium metal elements) in the coating layer.
[0019] In another embodiment, X further comprises other coating elements, and the other coating elements are one or more of W, Ti and Ce. Typical but non-limiting combinations include: a combination of W and Ce, a combination of W and Ti, a combination of Ti and Ce, and a combination of W, Ti and Ce.
[0020] In the present invention, among the X elements, while ensuring that the Al element accounts for more than 50 wt.%, other matching elements, such as one or more of W, Ti and Ce, may be introduced as appropriate.
[0021] In a second aspect, the present invention provides a method for preparing a positive electrode material having a coating layer as described in the first aspect, the preparation method comprising the following steps:
[0022] The positive electrode core and the coating source are mixed and sintered at a temperature of 350° C. to 500° C. to obtain a positive electrode material with a coating layer;
[0023] The coating source includes a cobalt source and an X source, the X source includes an aluminum source, and more than 50 wt.% of X is Al element.
[0024] Preferably, the cobalt source includes at least one of cobalt oxide, cobalt hydroxide and cobalt oxyhydroxide.
[0025] Preferably, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide and aluminum oxyhydroxide.
[0026] Preferably, the X source further includes other coating sources, and the elements in the other coating sources include at least one of W, Ti and Ce.
[0027] Preferably, the other coating source is at least one of nitrate, chloride, hydroxide or oxide.
[0028] Preferably, the sintering is performed in an oxygen-containing atmosphere. Exemplarily, the oxygen-containing atmosphere may be an air atmosphere or an oxygen atmosphere.
[0029] Preferably, the sintering time is 6h~24h.
[0030] Preferably, after the sintering is completed, the temperature is lowered at a cooling rate of 0.01° C. / min to 3° C. / min.
[0031] As a preferred technical solution of the method for preparing the positive electrode material with a coating layer according to the present invention, the method for preparing the positive electrode core comprises the following steps:
[0032] The nickel-cobalt hydroxide, the doping source and the lithium source are mixed and sintered to obtain a positive electrode core;
[0033] The doping elements in the doping source include Al and A, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.
[0034] Preferably, the lithium source is lithium hydroxide and / or lithium carbonate.
[0035] Preferably, during the preparation of the positive electrode core, the molar ratio of each element satisfies Li / (Ni+Co+Al+A) of 1 to 1.05.
[0036] Preferably, during the preparation of the positive electrode core, the sintering temperature is 400°C to 1000°C.
[0037] Preferably, during the preparation of the positive electrode core, the sintering time is 6 h to 20 h.
[0038] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the positive electrode comprises the positive electrode material with a coating layer as described in the first aspect.
[0039] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The positive electrode material of the present invention uses a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material as the core, which has good rate performance under high voltage. It is further coated with three lithium-cobalt compounds with different chemical compositions and Al elements are introduced into the coating layer. Since the morphology of lithium-cobalt compounds with different chemical compositions is different, it will affect the stability of the interface structure of the material itself. Therefore, by using spinel LiCoO2 as the main body of the coating layer, with a specific content of Li a Co 1-a Co2O4、Li b Co 1-b The synergistic effect of O and Al elements can stabilize the interface structure and reduce ohmic heat, thereby taking into account low heat generation and gas production, improving the stability of the material and the safety of lithium-ion batteries. Among them, the control of the following parameters is very critical: First, the mass ratio of X element to Co element in the coating layer is 50%~100%. This is because the introduction of X element may worsen the ohmic heat. Therefore, its coating amount cannot exceed the Co element. At the same time, in order to achieve the purpose of completely stabilizing the interface structure, its coating amount cannot be less than 50% of the Co coating amount. Second, the content of Co element in the coating layer is 1000ppm~4000ppm. If the content of Co element is too little, it will result in the inability to form a complete coating layer, and can only form a dispersed island coating, which will not achieve the technical effect of the coating at all; if the content of Co element is too much, it will result in Li without positive electrode activity. a Co 1-a Co2O4、Li b Co 1-bIf the O content is too high, the proportion of positive electrode active materials will be greatly reduced, thereby reducing the specific capacity of the entire material. In addition, it will significantly deteriorate the impedance of the positive electrode material, thereby affecting product performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a scanning electron microscope image of the positive electrode material with a coating layer provided in Example 1. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0044] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0045] In a cylindrical lithium-ion battery, a winding core is formed by stacking a positive electrode sheet, a separator, a negative electrode sheet, and a separator in this order and winding them up, and is housed in a battery case in a state of being impregnated with an electrolyte.
[0046] In one embodiment, a positive electrode active material layer is coated on both sides of a positive electrode foil to form a positive electrode sheet. The positive electrode foil may be a metal foil made of aluminum or an aluminum alloy.
[0047] In one embodiment, negative electrode active material layers are coated on both sides of the negative electrode foil to form a negative electrode sheet. The material of the negative electrode foil may be a metal foil made of copper or a copper alloy.
[0048] In one embodiment, the separator may be any separator known in the prior art of lithium-ion batteries.
[0049] In one embodiment, the negative electrode material may be a carbon material, such as a graphite material, wherein the graphite material may be artificial graphite and / or natural graphite, preferably a graphite composite negative electrode material doped with a certain amount of silicon oxygen or silicon carbon.
[0050] In one embodiment, the separator can be a PE film, a PP film or a composite film, wherein the composite film includes at least two of the PP film, the PE film and the PP film. Of course, in one embodiment, the separator can also be a ceramic-coated porous film.
[0051] In one embodiment, the electrolyte solution includes a solvent and an electrolyte salt.
[0052] In one embodiment, the solvent comprises any one or more of non-aqueous solvents such as organic solvents. The electrolyte of the non-aqueous solvent is a so-called non-aqueous electrolyte, and the non-aqueous solvent may be, for example, cyclic carbonate, chain carbonate, lactone, chain carboxylate, nitrile, etc. In addition, the electrolyte may further comprise any one or more of other materials such as additives.
[0053] In one embodiment, the aforementioned electrolyte salt may include, for example, any one or more of salts such as lithium salts. In addition, the electrolyte salt may also include salts other than lithium salts. The salts other than lithium salts may be, for example, light metal salts other than lithium.
[0054] In one example, the battery housing is a metal case, and the metal case may be a steel case or an aluminum case, and more preferably a steel case.
[0055] In the present invention, the dimensions of the cylindrical battery may be models such as 18650 and 21700.
[0056] Preferably, the following tests of the present invention are performed on 18650-type cylindrical battery cells.
[0057] In one embodiment, the present example provides a positive electrode material having a coating layer. The positive electrode material having a coating layer includes a positive electrode core and a coating layer covering the surface of the positive electrode core. The chemical composition of the positive electrode core is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x + y + z + m = 1, where A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba, and Ti;
[0058] The coating layer contains Co element and X element, and the mass ratio of X element to Co element in the coating layer is 50% - 100%; X is a metal element different from Co, and more than 50 wt.% of X is Al element;
[0059] The coating layer includes lithium cobalt compounds, and the lithium cobalt compounds include Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2, where 0 < a < 1, 0 < b < 1. The contents of Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2 in the total mass of the three are 1 wt.% - 15 wt.%, 10 wt.% - 25 wt.%, and 65 wt.% - 76 wt.%, respectively, and the content of Li b Co 1-b O is greater than that of Li a Co1-a Content of Co2O4;
[0060] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 1000 ppm to 4000 ppm.
[0061] In one embodiment of the present invention, 1 ≤ α ≤ 1.05, for example, it can be 1, 1.01, 1.02, 1.03, 1.04 or 1.05, etc.; 0.80 ≤ x ≤ 0.95, for example, it can be 0.80, 0.82, 0.83, 0.85, 0.88, 0.89, 0.90, 0.92, 0.93, 0.94 or 0.95, etc.; 0.04 ≤ y ≤ 0.15, for example, it can be 0.04, 0.06, 0.08, 0.10, 0.12, 0.13, 0.14 or 0.15, etc.; 0.005 ≤ z ≤ 0.06, for example, it can be 0.01, 0.02, 0.03, 0.04, 0.05 or 0.06, etc.; 0 ≤ m ≤ 0.02, for example, it can be 0, 0.001, 0.003, 0.005, 0.007, 0.008, 0.01, 0.012, 0.015, 0.017 or 0.02, etc. Among them, when m is 0, it means that the chemical composition does not contain element A.
[0062] In one embodiment of the present invention, Li a Co 1-a For a in Co2O4, 0 < a < 1. Exemplarily, a can be 0.01, 0.03, 0.05, 0.07, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85 or 0.9, etc.
[0063] In one embodiment of the present invention, Li b Co 1-b For b in O, 0 < b < 1. Exemplarily, b can be 0.01, 0.03, 0.05, 0.07, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85 or 0.9, etc.
[0064] In one embodiment of the present invention, Li a Co 1-a The content of Co2O4 is 1 wt.% to 15 wt.%, for example, it can be 1 wt.%, 2 wt.%, 4 wt.%, 5 wt.%, 7 wt.%, 8 wt.%, 10 wt.%, 12 wt.%, 13 wt.% or 15 wt.%, etc.
[0065] In one embodiment of the present invention, Li b Co 1-b The content of O is 10wt.%~25wt.%, for example, it can be 10wt.%, 12wt.%, 13wt.%, 15wt.%, 16wt.%, 18wt.%, 19wt.%, 20wt.%, 21wt.%, 23wt.% or 25wt.%, etc.
[0066] In one embodiment of the present invention, the content of LiCoO2 is 65wt.%~76wt.%, for example, it can be 65wt.%, 66wt.%, 68wt.%, 70wt.%, 72wt.%, 74wt.%, 75wt.% or 76wt.%, etc.
[0067] In one embodiment of the present invention, the mass ratio of the X element to the Co element in the coating layer is 50% to 100%, for example, it can be 50%, 52%, 55%, 58%, 60%, 62.5%, 65%, 67%, 70%, 73%, 76%, 78%, 80%, 83%, 85%, 88%, 90%, 92%, 94%, 95%, 96%, 98% or 100%.
[0068] In one embodiment of the present invention, the content of Co element in the coating layer is 1000ppm~4000ppm, for example, it can be 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1800ppm, 2000ppm, 2200ppm, 2300ppm, 2500ppm, 2600ppm, 2800ppm, 3000ppm, 3150ppm, 3300ppm, 3400ppm, 3500ppm, 3600ppm, 3800ppm or 4000ppm, etc.
[0069] The positive electrode material of one embodiment of the present invention uses a high-nickel nickel-cobalt-aluminum-based ternary positive electrode material as the core, which has good rate performance under high voltage. It is further coated with three lithium-cobalt compounds with different chemical compositions and Al elements are introduced into the coating layer. Since the morphology of lithium-cobalt compounds with different chemical compositions is different, it will affect the stability of the interface structure of the material itself. Therefore, by using spinel LiCoO2 as the main body of the coating layer, with a specific content of Li a Co 1- a Co2O4、Li b Co 1-bThe synergistic effect of O and Al elements can stabilize the interface structure and reduce ohmic heat, thereby taking into account low heat generation and gas production, improving the stability of the material and the safety of lithium-ion batteries. Among them, the control of the following parameters is very critical: First, the mass ratio of X element to Co element in the coating layer is 50%~100%. This is because the introduction of X element may worsen the ohmic heat. Therefore, its coating amount cannot exceed the Co element. At the same time, in order to achieve the purpose of completely stabilizing the interface structure, its coating amount cannot be less than 50% of the Co coating amount. Second, the content of Co element in the coating layer is 1000ppm~4000ppm. If the content of Co element is too little, less than 1000ppm, it will result in the inability to form a complete coating layer, and only a dispersed island coating can be formed, and the technical effect of the coating cannot be achieved at all. If the content of Co element is too much, it will result in Li without positive electrode activity. a Co 1-a Co2O4、Li b Co 1-b If the O content is too high, the proportion of positive electrode active materials will be greatly reduced, thereby reducing the specific capacity of the entire material. In addition, it will significantly deteriorate the impedance of the positive electrode material, thereby affecting product performance.
[0070] In one embodiment, the mass ratio of the X element in the coating layer to the Co element in the coating layer is greater than or equal to 50% and less than 100%, and in this case, the contents of the two are different.
[0071] In another embodiment, the mass ratio of the X element in the coating layer to the Co element in the coating layer is 100%, that is, the contents of the two are the same. In one embodiment, X is 100wt.% of Al element. Therefore, the coating layer contains Co element and Al element, and the mass ratio of the Al element in the coating layer to the Co element in the coating layer is 50% to 100%.
[0072] In one embodiment, the total mass of the Co element and the X element in the coating layer is ω1, and the total mass of the metal elements (excluding lithium metal elements) in the coating layer is ω2, then ω1 / ω2≥90%, for example, it can be 90%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 99.5% or more, preferably ≥95%. That is, the Co element and the X element in the coating layer account for more than 90% of the mass ratio of the total metal elements (excluding lithium metal elements) in the coating layer, and more preferably 95%.
[0073] In the present invention, if other metals and other trace metal doping are not considered, the Co element and the X element in the coating layer of the present invention can account for nearly 100% of the total metal elements (excluding lithium metal elements) in the coating layer.
[0074] In one embodiment, when X is 100% Al, the Co and Al elements in the coating layer account for more than 90% of the total mass ratio of the metal elements (excluding lithium metal elements) in the coating layer, and more preferably 95%. In the present invention, if other metals and other trace metal doping are not considered, the Co and Al elements in the coating layer of the present invention can account for nearly 100% of the total mass ratio of the metal elements (excluding lithium metal elements) in the coating layer.
[0075] In one embodiment, X further comprises other coating elements, and the other coating elements are one or more of W, Ti and Ce. Typical but non-limiting combinations include: a combination of W and Ce, a combination of W and Ti, a combination of Ti and Ce, and a combination of W, Ti and Ce.
[0076] In one embodiment, among the X elements, while ensuring that the Al element accounts for more than 50 wt.%, other matching elements, such as one or more of W, Ti and Ce, may be introduced as appropriate.
[0077] For the introduction of W and Ce, X includes Al, W and Ce at the same time. Al cooperates with W and Ce. W and Ce are used to further cooperate with Al to reduce the surface impedance of the coating layer, which is beneficial to further reduce the DC internal resistance of the battery cell. At the same time, if the content of W and Ce is too large, it will affect the high-temperature storage, high-rate charge and discharge performance of the battery cell. Therefore, it should be ensured that the Al element accounts for more than 50wt.% of the X element.
[0078] Regarding the introduction of Ti, X includes both Al and Ti at this time. Al and Ti cooperate, and Ti can further reduce the surface impedance of the coating layer, which is beneficial to further reduce the DC internal resistance of the battery cell. At the same time, if the Ti content is too large, the capacity of the battery cell will be reduced. Therefore, it should be ensured that the Al element accounts for more than 50wt.% of the X element.
[0079] In one embodiment of the present invention, there may also be a certain amount of Co source or cobalt compound after the reaction of Co source in the coating layer. The Co source or cobalt compound may include, for example, cobalt oxide, cobalt hydroxide, cobalt oxyhydroxide, etc. The Co source is generally an unreacted Co source when preparing the positive electrode material, and the cobalt compound is generally a substance formed by the reaction of the unreacted Co source during the second sintering process when preparing the positive electrode material. In one embodiment, the unreacted Co source accounts for less than 12% of the total mass of the Co source used in the coating process, and more preferably less than 5%. Obviously, the unreacted or Co source has no obvious benefit or damage to the coating, and is only generated by the sintering temperature in the preparation method, and belongs to the possible unreacted substances when the secondary sintering adopts a low temperature.
[0080] In another embodiment, the present invention provides a method for preparing a cathode material with a coating layer as described above. The preparation method includes the following steps:
[0081] Mix the cathode core with a coating source and then sinter at a temperature of 350°C to 500°C to obtain a cathode material with a coating layer;
[0082] Among them, the coating source includes a cobalt source and an X source. The X source includes an aluminum source, and more than 50 wt.% of X is Al element.
[0083] In the method for preparing a cathode material with a coating layer provided by an embodiment of the present invention, the sintering temperature is 350°C to 500°C, for example, it can be 350°C, 370°C, 400°C, 425°C, 450°C, 475°C or 500°C, etc. The preparation process of the cathode core generally uses a lithium source and other raw materials to be prepared through a first sintering. Generally, there are residual Li substances on its surface. The method of the present invention uses a coating source containing a cobalt source and an aluminum source to mix and sinter the cathode core at a low temperature. The Co element mainly reacts with the residual Li substances on the surface of the cathode core to form three different lithium cobalt compounds with different chemical compositions within a specific temperature range, realizing the synergistic effect of various morphologies. At the same time, due to the presence of the aluminum source, the Al element can improve the interface stability, so that the cathode material can take into account low gas generation and heat generation.
[0084] When the inventors completed this technical solution, it was found that within the temperature range of 350°C to 500°C, the cobalt source was basically reacted to form lithium cobalt oxide during the secondary sintering (generally, the sintering involved in the preparation process of the cathode core is defined as the first sintering, then the sintering here is defined as the secondary sintering). The mass of the unreacted cobalt source only accounts for less than 12% of the mass of the cobalt source used in the coating process, preferably less than 5%.
[0085] Further, the reacted cobalt source is basically completely converted into Li a Co 1-a Co2O4 (0 < a < 1), Li b Co 1-b O (0 < b < 1) and LiCoO2. Among these three lithium cobalt oxides, the contents of Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 in the lithium cobalt oxides account for 1 wt.% to 15 wt.%, 10 wt.% to 25 wt.% and 65 wt.% to 76 wt.%, respectively.
[0086] From 350°C to 500°C, we can generally observe the following rule: Li a Co1-a The upper limit of Co2O4 at 350℃ is 15wt.% and the content is rapidly reduced to about 1wt.%. a Co 1-a The amount of Co2O4 is very small, but we can still observe Li a Co 1-a Co2O4 is also present in the coating layer. We can also observe Li b Co 1-b O increases from 10 wt.% at 350°C to 25 wt.% at 500°C, while the content of LiCoO2 remains roughly stable in the temperature range from 350°C to 500°C, roughly showing a slight upward trend in the range of 65wt.%-76 wt.%.
[0087] In one embodiment, the total mass of the Co element and the X element in the coating layer is ω1, and the total mass of the metal element in the coating layer is ω2, then ω1 / ω2≥90%, preferably ≥98%.
[0088] In one embodiment, ω1 / ω2 is 100%.
[0089] In one embodiment, the cobalt source includes at least one of cobalt oxide, cobalt hydroxide, and cobalt oxyhydroxide.
[0090] In one embodiment, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum oxyhydroxide.
[0091] In one embodiment, the X source further includes other coating sources, and the elements in the other coating sources are at least one of W, Ti and Ce.
[0092] In one embodiment, the other coating source is at least one of nitrate, chloride, hydroxide or oxide.
[0093] Illustratively, the other coating sources may be one or more of tungsten nitrate, tungsten chloride, tungsten hydroxide, tungsten oxide, titanium nitrate, titanium chloride, titanium hydroxide, titanium oxide, cerium nitrate, cerium chloride, cerium hydroxide or cerium oxide.
[0094] In one embodiment, the sintering is performed in an oxygen-containing atmosphere. For example, the oxygen-containing atmosphere may be an air atmosphere or an oxygen atmosphere.
[0095] In one embodiment, the sintering time is 6 h to 24 h, for example, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h.
[0096] In one embodiment, after the sintering is completed, the temperature is cooled at a cooling rate of 0.01°C / min to 3°C / min. For example, the cooling rate can be 0.01°C / min, 0.05°C / min, 0.1°C / min, 0.2°C / min, 0.5°C / min, 0.7°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min, etc.
[0097] In one embodiment, the method for preparing the positive electrode core comprises the following steps:
[0098] The nickel-cobalt hydroxide, the doping source and the lithium source are mixed and sintered to obtain a positive electrode core;
[0099] The doping elements in the doping source include Al and A, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.
[0100] In one embodiment, the lithium source is lithium hydroxide and / or lithium carbonate.
[0101] In one embodiment, during the preparation of the positive electrode core, the molar ratio of each element satisfies Li / (Ni+Co+Al+A) of 1 to 1.05, for example, it can be 1, 1.01, 1.02, 1.03, 1.04 or 1.05, etc.
[0102] In one embodiment, during the preparation of the positive electrode core, the sintering temperature is 400°C~1000°C, for example, it can be 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, etc.
[0103] In one embodiment, during the preparation of the positive electrode core, the sintering time is 6 h to 20 h, for example, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h.
[0104] In another embodiment, the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the positive electrode comprises the positive electrode material with a coating layer.
[0105] Based on the above embodiments, the following typical but non-limiting examples are provided:
[0106] Example 1
[0107] This embodiment provides a cathode material with a coating layer. The cathode material with a coating layer includes a cathode core and a coating layer coated on the surface of the cathode core. The cathode core is a nickel-cobalt-aluminum ternary cathode material (chemical formula: Li 1.03 (Ni 0.88 Co 0.10 Al 0.02 )O2). The coating layer includes a lithium cobalt compound, and the lithium cobalt compound includes Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2, where 0 < a < 1 and 0 < b < 1. Based on the total mass of Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2 being 100 wt.%, the contents of Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2 are 3 wt.%, 23 wt.%, and 74 wt.%, respectively;
[0108] The coating layer further includes Al element, and the Al element exists in the form of Al2O3;
[0109] Based on the total mass of the cathode core, the content of Co element in the coating layer is 1000 ppm, and the content of Al element is 800 ppm. Then, the mass ratio of Al element to Co element in the coating layer is 80%.
[0110] Figure 1 is the scanning electron microscope image of the cathode material with a coating layer provided by this embodiment.
[0111] This embodiment also provides a preparation method of the above-mentioned cathode material with a coating layer, including the following steps:
[0112] (1) Prepare the cathode core:
[0113] Mix nickel-cobalt hydroxide, a doping source, and a lithium source, and then perform a first sintering to obtain the cathode core. Among them, the doping source is aluminum oxide, the lithium source is LiOH, the molar ratio of Li / (Ni + Co + Al) is 1.03, the sintering temperature is 700 °C, and the sintering time is 16 h.
[0114] (2) Coating process:
[0115] The positive electrode core is mixed and ground with a coating source. After uniform grinding, it is subjected to secondary sintering. The sintering is carried out in an air atmosphere. The sintering temperature is 485 °C, and the sintering time is 8 h. After sintering is completed, the temperature is decreased at a rate of 2 °C / min to obtain a positive electrode material with a coating layer; wherein, the coating source is cobalt hydroxide and aluminum hydroxide.
[0116] Example 2
[0117] This example provides a positive electrode material with a coating layer. The positive electrode material with a coating layer includes a positive electrode core and a coating layer coated on the surface of the positive electrode core. The positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula: Li 1.01 (Ni 0.85 Co 0.12 Al 0.025 Zr 0.005 )O2). The coating layer includes a lithium cobalt compound. The lithium cobalt compound includes Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2. Among them, 0 < a < 1, 0 < b < 1. Based on the total mass of the Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 being 100 wt.%, the contents of the Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 are 8 wt.%, 18 wt.% and 74 wt.% respectively; the coating layer also includes a cobalt source. The cobalt source is cobalt oxide, and the mass of the cobalt source accounts for 13 wt.% of the total mass of the cobalt source used in the coating process;
[0118] The coating layer also includes Al element. The Al element exists in the form of Al2O3;
[0119] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 3000 ppm, and the content of Al element is 2000 ppm. Then the mass ratio of Al element to Co element in the coating layer is 66.7%.
[0120] This example also provides a preparation method of the above positive electrode material with a coating layer, including the following steps:
[0121] (1) Prepare a positive electrode core:
[0122] Mix nickel cobalt hydroxide, doping source and lithium source, and then conduct a primary sintering to obtain a cathode core; wherein, the doping source is aluminum oxide and zirconium oxide, the lithium source is Li2CO3, the molar ratio of Li / (Ni+Co+Al) is 1.01, the sintering temperature is 750°C, and the sintering time is 20h.
[0123] (2)Coating process:
[0124] Mix the cathode core and the coating source, grind them evenly, and then conduct a secondary sintering. The sintering is carried out in an oxygen atmosphere, the sintering temperature is 400°C, the sintering time is 12h, and after the sintering is completed, the temperature is decreased at a rate of 0.5°C / min to obtain a cathode material with a coating layer; wherein, the coating source is cobalt oxide and aluminum oxide.
[0125] Example 3
[0126] This example provides a cathode material with a coating layer. The cathode material with a coating layer includes a cathode core and a coating layer coated on the surface of the cathode core. The cathode core is a nickel cobalt aluminum ternary cathode material (chemical formula: Li 1.05 (Ni 0.90 Co 0.09 Al 0.009 Mg 0.001 )O2), the coating layer includes a lithium cobalt compound, and the lithium cobalt compound includes Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2, where 0 < a < 1, 0 < b < 1. Based on the total mass of the Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 being 100wt.%, the contents of the Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 are 14wt.%, 15wt.% and 71wt.% respectively; the coating layer also includes cobalt oxide, and the mass of cobalt oxide accounts for 11wt.% of the total mass of the cobalt source used in the coating process;
[0127] The coating layer also includes Al element, and the Al element exists in the form of Al2O3;
[0128] Based on the total mass of the cathode core, the content of Co element in the coating layer is 4000ppm, and the content of Al element is 2000ppm, so the mass ratio of Al element to Co element in the coating layer is 50%.
[0129] This embodiment also provides a method for preparing the above-mentioned cathode material with a coating layer, comprising the following steps:
[0130] (1) Prepare the cathode core:
[0131] Mix nickel cobalt hydroxide, a doping source, and a lithium source and then perform a first sintering to obtain the cathode core; wherein, the doping source is alumina and magnesia, the lithium source is Li2CO3, the molar ratio of Li / (Ni + Co + Al) is 1.05, the sintering temperature is 690 °C, and the sintering time is 14 h.
[0132] (2) Coating process:
[0133] Mix the cathode core and a coating source and grind them evenly, then perform a second sintering. The sintering is carried out in an oxygen atmosphere, the sintering temperature is 350 °C, the sintering time is 9 h, and after sintering is completed, the temperature is decreased at a rate of 0.5 °C / min to obtain the cathode material with a coating layer; wherein, the coating source is cobalt hydroxide and alumina.
[0134] Example 4
[0135] This embodiment provides a cathode material with a coating layer. The cathode material with a coating layer includes a cathode core and a coating layer coated on the surface of the cathode core. The cathode core is a nickel cobalt aluminum ternary cathode material (chemical formula: Li(Ni 0.83 Co 0.11 Al 0.05 Zr 0.002 Mg 0.002 La 0.002 Sr 0.004 )O2), and the coating layer includes a lithium cobalt compound. The lithium cobalt compound includes Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2, where 0 < a < 1, 0 < b < 1. Based on the total mass of the Li a Co 1- a Co2O4, Li b Co 1-b O, and LiCoO2 being 100 wt.%, the Li a Co 1-a Co2O4, Li b Co 1-bThe contents of O and LiCoO₂ are 4 wt.%, 22 wt.% and 74 wt.% respectively; the coating layer further includes a cobalt source, the cobalt source is cobalt oxide, and the mass of the cobalt source accounts for 10 wt.% of the total mass of the cobalt source used in the coating process;
[0136] The coating layer further includes Al element, and the Al element exists in the form of Al₂O₃;
[0137] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 1500 ppm, and the content of Al element is 1500 ppm, then the mass ratio of Al element to Co element in the coating layer is 100%.
[0138] This embodiment also provides a preparation method of the above positive electrode material with a coating layer, including the following steps:
[0139] (1) Prepare the positive electrode core:
[0140] Mix nickel-cobalt hydroxide, doping source and lithium source and then perform a primary sintering to obtain the positive electrode core; wherein, the doping source is aluminum oxide, zirconium oxide, magnesium hydroxide, lanthanum oxide and strontium oxide, the lithium source is Li₂CO₃, the molar ratio of Li / (Ni + Co + Al) is 1, the sintering temperature is 690 °C, and the sintering time is 14 h.
[0141] (2) Coating process:
[0142] Mix and grind the positive electrode core and the coating source, and perform a secondary sintering after grinding evenly. The sintering is carried out in an air atmosphere, the sintering temperature is 450 °C, the sintering time is 6 h, and after sintering, the temperature is reduced at a rate of 0.6 °C / min to obtain the positive electrode material with a coating layer; wherein, the coating source is cobalt oxide and aluminum oxide.
[0143] Example 5
[0144] This embodiment provides a positive electrode material with a coating layer. The positive electrode material with a coating layer includes a positive electrode core and a coating layer coated on the surface of the positive electrode core. The positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula is Li 1.04 (Ni 0.92 Co 0.07 Al 0.01 )O₂), the coating layer includes a lithium cobalt compound, and the lithium cobalt compound includes Li a Co 1-a Co₂O₄, Li b Co 1-b O and LiCoO₂, where 0 < a < 1, 0 < b < 1, based on the Li a Co 1-a Co₂O₄, Lib Co 1-b The total mass of LiO and LiCoO2 is 100wt.%, and the Li a Co 1-a Co2O4、Li b Co 1-b The contents of O and LiCoO2 are 2wt.%, 23wt.% and 75wt.% respectively;
[0145] The coating layer also includes Al element, which exists in the form of Al2O3;
[0146] Taking the total mass of the positive electrode core as a reference, the content of Co element in the coating layer is 2000ppm, the content of Al element is 1000ppm, and the content of W element is 1000ppm, then the mass ratio of the total content of Al element and W element in the coating layer to the Co element is 100%.
[0147] This embodiment also provides a method for preparing the positive electrode material having a coating layer, comprising the following steps:
[0148] (1) Preparation of positive electrode core:
[0149] Nickel cobalt hydroxide, a doping source and a lithium source are mixed and sintered once to obtain a positive electrode core; wherein the doping source is aluminum oxide, the lithium source is Li2CO3, the Li / (Ni+Co+Al) molar ratio is 1.04, the sintering temperature is 600°C, and the sintering time is 14 hours.
[0150] (2) Coating process:
[0151] The positive electrode core and the coating source are mixed and ground, and after grinding evenly, secondary sintering is performed. The sintering is performed in an oxygen atmosphere at a temperature of 500°C and a sintering time of 10 hours. After sintering, the temperature is cooled at a cooling rate of 2°C / min to obtain a positive electrode material with a coating layer; wherein the coating source is cobalt oxide, aluminum oxide and tungsten oxide.
[0152] Example 6
[0153] This embodiment provides a positive electrode material with a coating layer, wherein the positive electrode material with a coating layer comprises a positive electrode core and a coating layer coated on the surface of the positive electrode core, wherein the positive electrode core is a nickel-cobalt-aluminum ternary positive electrode material (chemical formula is Li 1.02 (Ni 0.90 Co 0.07 Al 0.02 La 0.005 )O2), the coating layer includes a lithium cobalt compound, the lithium cobalt compound includes Li a Co 1-a Co2O4、Lib Co 1-b O and LiCoO2, where 0 < a < 1, 0 < b < 1, based on the total mass of the Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 being 100 wt.%, the contents of the Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 are 2 wt.%, 23 wt.% and 75 wt.%, respectively;
[0154] The coating layer further includes Al element, and the Al element exists in the form of Al2O3;
[0155] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 2000 ppm, the content of Al element is 1000 ppm, and the content of W element is 1000 ppm, then the mass ratio of Al element to Co element in the coating layer is 100%.
[0156] This embodiment also provides a preparation method of the above positive electrode material with a coating layer, including the following steps:
[0157] (1) Prepare the positive electrode core:
[0158] Mix nickel cobalt hydroxide, doping source and lithium source and then perform primary sintering to obtain the positive electrode core; among them, the doping source is aluminum oxide and lanthanum oxide, the lithium source is Li2CO3, the Li / (Ni + Co + Al) molar ratio is 1.02, the sintering temperature is 600 °C, and the sintering time is 14 h.
[0159] (2) Coating process:
[0160] Mix the positive electrode core and the coating source and grind them evenly, then perform secondary sintering. The sintering is carried out in an oxygen atmosphere, the sintering temperature is 500 °C, the sintering time is 10 h, and after sintering, the temperature is decreased at a rate of 2 °C / min to obtain the positive electrode material with a coating layer; among them, the coating source is cobalt oxide, aluminum oxide and tungsten oxide.
[0161] Example 7
[0162] This embodiment provides a positive electrode material with a coating layer. The positive electrode material with a coating layer includes a positive electrode core and a coating layer coated on the surface of the positive electrode core. The positive electrode core is a nickel cobalt aluminum ternary positive electrode material (chemical formula is Li 1.02 (Ni 0.90 Co 0.07 Al0.02 La 0.005 )O2), the coating layer includes a lithium cobalt compound, and the lithium cobalt compound includes Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2, where 0 < a < 1, 0 < b < 1. Based on the total mass of the Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 being 100 wt.%, the contents of the Li a Co 1-a Co2O4, Li b Co 1-b O and LiCoO2 are 8 wt.%, 18 wt.% and 74 wt.%, respectively;
[0163] The coating layer also includes Al element, and the Al element exists in the form of Al2O3;
[0164] Based on the total mass of the positive electrode core, the content of Co element in the coating layer is 2000 ppm, the content of Al element is 1000 ppm, and the content of Ti element is 500 ppm. Then the mass ratio of Al + Ti element to Co element in the coating layer is 75%.
[0165] This embodiment also provides a preparation method of the above positive electrode material with a coating layer, including the following steps:
[0166] (1) Prepare the positive electrode core:
[0167] Mix nickel cobalt hydroxide, doping source and lithium source and conduct primary sintering to obtain the positive electrode core; among them, the doping source is aluminum oxide and lanthanum oxide, the lithium source is Li2CO3, the molar ratio of Li / (Ni + Co + Al) is 1.02, the sintering temperature is 600 °C, and the sintering time is 14 h.
[0168] (2) Coating process:
[0169] Mix the positive electrode core and the coating source and grind them evenly, then conduct secondary sintering. The sintering is carried out in an oxygen atmosphere, the sintering temperature is 500 °C, the sintering time is 10 h, and after sintering, cool down at a cooling rate of 2 °C / min to obtain the positive electrode material with a coating layer; among them, the coating source is cobalt oxide, aluminum oxide and tungsten oxide.
[0170] Comparative Example 1
[0171] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the difference is that, based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 1000ppm, and the content of the Al element is 3000ppm, then the mass ratio of the Al element to the Co element in the coating layer is 300%; the types and contents of the Co element and the X element in the coating layer are shown in Table 1.
[0172] Comparative Example 2
[0173] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the only difference is that, based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 1000ppm, and the content of the Al element is 400ppm, then the mass ratio of the Al element to the Co element in the coating layer is 40%; the types and contents of the Co element and the X element in the coating layer are shown in Table 1.
[0174] Comparative Example 3
[0175] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the only difference is that the temperature of the secondary sintering is changed to 300° C. The types and contents of the Co element and the X element in the coating layer are shown in Table 1.
[0176] Comparative Example 4
[0177] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the only difference is that the temperature of the secondary sintering is changed to 600° C. The types and contents of the Co element and the X element in the coating layer are shown in Table 1.
[0178] Comparative Example 5
[0179] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the only difference is that the content of the Co element in the coating layer is replaced from 1000 ppm to 800 ppm.
[0180] Comparative Example 6
[0181] This comparative example provides a positive electrode material with a coating layer. Compared with Example 1, the only difference is that the content of the Co element in the coating layer is replaced from 1000 ppm to 4200 ppm.
[0182] The parameters and preparation parameters of the positive electrode materials provided in Examples 1-6 and Comparative Examples 1-6 are shown in Table 1, wherein Li x Co 1-x Co2O4、Li b Co 1-b The contents of O and LiCoO2 are determined by Li x Co 1-xCo2O4、Li b Co 1-b The total mass of O and LiCoO2 is 100 wt.%.
[0183] Table 1
[0184]
[0185] Prepare the battery:
[0186] (1) Preparation of positive electrode sheet:
[0187] The positive electrode materials of Examples 1-7 and Comparative Examples 1-6 were used as active materials, and the active materials were mixed with a conductive agent Super P and a binder PVDF in NMP at a mass ratio of 95:2:3 to obtain a positive electrode slurry. The positive electrode slurry was coated on the surface of an aluminum foil and dried to obtain a positive electrode sheet.
[0188] (2) Preparation of negative electrode sheet:
[0189] The artificial graphite negative electrode, the conductive agent Super P, the binder CMC, and the thickener SBR were mixed in water at a mass ratio of 96:0.5:1.5:2 to obtain a negative electrode slurry. The negative electrode slurry was coated on the surface of the copper foil and dried to obtain a negative electrode sheet.
[0190] (3) Providing a diaphragm and an electrolyte, wherein the diaphragm is a multilayer composite diaphragm, the substrate material is a polyolefin polymer, and the composite material is a high heat-resistant inorganic ceramic; the electrolyte is obtained by dissolving LiPF6 in a mixed solvent of EC, DMC and FEC, wherein the mass ratio of EC:DMC:FEC:LiPF6 is 20:60:5:15.
[0191] (4) The positive electrode sheet, negative electrode sheet and separator are wound up, placed in a battery case and injected with electrolyte to obtain a battery.
[0192] To perform a performance test on the battery:
[0193] (1) Test cycle performance: at room temperature 25°C, charge at 2C, discharge at 10C, cycle 600 times, calculate capacity retention rate, capacity retention rate = 600th cycle discharge capacity / first cycle discharge capacity × 100%.
[0194] (2) Test the maximum temperature of a fully charged cell: The test is carried out in a hot box at a temperature of 133°C.
[0195] (3) Test the maximum temperature of a single cell when it is overcharged to 6V at 5C, the CID opening time, and check whether the cell catches fire or explodes. Among them, the maximum temperature of a single cell when it is overcharged to 6V at 5C reflects the heat generation, and the CID opening time reflects the gas generation. A delayed CID opening time indicates less gas generation. At the same time, the present invention hopes that the CID will open when the overcharge is close to 5V, so the CID opening time should not be too early or too late. If it is opened too early, it will show that the CID has been opened before the battery is charged to 5V, and the cell is disconnected, which will prematurely cause the battery or even the battery pack to fail. However, if it is opened too late, the battery is prone to overheating and explosion. At this time, the overcharge voltage of the battery has obviously seriously exceeded 5V, and the battery will be in a very critical state.
[0196] See Table 2 for the results.
[0197] Table 2
[0198]
[0199] It can be seen from the above that when the secondary sintering temperature exceeds 500°C, for example, the secondary sintering temperature in Comparative Example 4 is 600°C, Li a Co 1-a Co2O4、Li b Co 1-b Among the three lithium cobalt oxides, LiCoO2 and LiCoO2, the relative content of LiCoO2 will exceed 76wt.% and rise to more than 80wt.%. LiCoO2 gradually occupies a dominant position and gradually transforms into a layered oxide. Its lattice oxygen is very easy to escape under high voltage conditions, causing the collapse of the positive electrode material structure, and then reacting with the electrolyte to cause thermal runaway of the battery cell.
[0200] When the secondary sintering temperature is lower than 350°C, for example, the secondary sintering temperature in Comparative Example 3 is 300°C, we found that Li a Co 1-a Co2O4、Li b Co 1-b The relative contents of O and LiCoO2 are 16 wt.%, 14 wt.% and 70 wt.%. a Co 1-aThe content of Co2O4 is less than 15wt.%, its capacity retention rate is reduced, and an explosion also occurred in the experiment. Therefore, the technical solution of the present invention cannot be realized, and the corresponding technical effect cannot be achieved. As shown in Table 2, by regulating the type and content of the lithium cobalt compound in the surface coating layer of the positive electrode material, the content of the Co element, and the mass ratio of the Co element to other elements in the coating layer, the positive electrode material exhibits the following properties: enhanced interface stability and reduced gas production. The 2C / 10C cycle capacity retention rate of the 18650 cylindrical battery assembled from the positive electrode materials of Examples 1-6 is greater than 80% after 600 cycles, and the maximum temperature of the fully charged battery is above 128°C, and it will not be discharged due to gas production. Moreover, even when the single battery cell 5C is overcharged to 5V, the maximum temperature exceeds 100°C, and it will not catch fire and explode. Among them, the single battery cell of Example 3 has the highest temperature when overcharged, indicating that under this design, the interface protection effect is the best, and even if the maximum temperature of the battery cell exceeds 120°C, the battery cell will not catch fire and explode.
[0201] It can be seen from Examples 1-7 that the CID opening time is between 700s and 820s, which is a more suitable design range for the present invention, indicating that the CID is opened when the battery is overcharged to close to 5V, indicating that the battery is in good use. If it is opened too early, it will show that the CID has been opened before the battery is charged to 5V, and the battery cell is disconnected, which prematurely causes the battery and even the battery pack to fail. Moreover, if it is opened too late, it does not belong to the technical solution required by the present invention. When the CID opening time is over, it is easy to cause risks such as overheating and explosion inside the battery. At this time, the overcharge voltage of the battery has obviously seriously exceeded 5V, and the battery will be in a very critical state.
[0202] In comparative example 1, the mass ratio of Al to Co is greater than 100%. Although the CID opening time is delayed, indicating that the gas production is small, the surface impedance deteriorates significantly, and the battery cell catches fire and explodes. In comparative example 2, the mass ratio of Al to Co is less than 50%, resulting in a decrease in cycle performance, and fire and explosion occurred at the highest temperature of the fully charged battery cell. It can be seen that the ratio of other elements in the coating layer to Co must meet 50% to 100%, otherwise it will not be possible to balance low gas production and heat production.
[0203] The content of Co element in the coating layer of Comparative Example 5 is too little, and the content of Co element in the coating layer of Comparative Example 6 is too much, both of which result in failure to achieve both low gas production and low heat production.
[0204] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A positive electrode material having a coating layer, characterized in that: The positive electrode material with a coating layer comprises a positive electrode core and a coating layer coated on the surface of the positive electrode core, and the chemical composition of the positive electrode core is Li α Ni x Co y Al z A m O2, 1≤α≤1.05, 0.80≤x≤0.95, 0.04≤y≤0.15, 0.005≤z≤0.06, 0≤m≤0.02, x+y+z+m=1, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti; The coating layer contains Co element and X element, the mass ratio of X element in the coating layer to Co element in the coating layer is 50% to 100%; X is a metal element different from Co, and more than 50wt.% of X is Al element; The coating layer includes lithium cobalt oxide, and the lithium cobalt oxide includes Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2, where 0 < a < 1, 0 < b < 1. The contents of Li a Co 1-a Co2O4, Li b Co 1-b O, and LiCoO2 in the total mass of the three are 1 wt.% - 15 wt.%, 10 wt.% - 25 wt.%, and 65 wt.% - 76 wt.%, respectively, and the content of Li b Co 1-b O is greater than the content of Li a Co 1-a Co2O4; Based on the total mass of the positive electrode core, the content of the Co element in the coating layer is 1000ppm~4000ppm.
2. The positive electrode material with a coating layer according to claim 1, characterized in that: X is 100 wt.% of Al element.
3. The positive electrode material with a coating layer according to claim 1, characterized in that: X also includes other coating elements, and the other coating elements are one or more of W, Ti and Ce.
4. A method for preparing a positive electrode material having a coating layer as claimed in any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: The positive electrode core and the coating source are mixed and sintered at a temperature of 350° C. to 500° C. to obtain a positive electrode material with a coating layer; The coating source includes a cobalt source and an X source, the X source includes an aluminum source, and more than 50 wt.% of X is Al element.
5. The preparation method according to claim 4, characterized in that: The cobalt source comprises at least one of cobalt oxide, cobalt hydroxide and cobalt oxyhydroxide; and / or, The aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum oxyhydroxide.
6. The preparation method according to claim 4, characterized in that: The X source also includes other coating sources, and the elements in the other coating sources are at least one of W, Ti and Ce; and / or, The other coating source is at least one of nitrate, chloride, hydroxide or oxide.
7. The preparation method according to claim 4, characterized in that: The sintering is performed in an oxygen-containing atmosphere; and / or, The sintering time is 6h~24h; and / or, After the sintering is completed, the temperature is lowered at a cooling rate of 0.01° C. / min to 3° C. / min.
8. The preparation method according to claim 4, characterized in that: The method for preparing the positive electrode core comprises the following steps: The nickel-cobalt hydroxide, the doping source and the lithium source are mixed and sintered to obtain a positive electrode core; The doping elements in the doping source include Al and A, wherein A includes one or more of Zr, Mg, Sr, Y, La, Nb, Ba and Ti.
9. The preparation method according to claim 8, characterized in that: During the preparation of the positive electrode core, the molar ratio of each element satisfies Li / (Ni+Co+Al+A) of 1 to 1.05; and / or, During the preparation of the positive electrode core, the sintering temperature is 400° C. to 1000° C.; and / or, During the preparation of the positive electrode core, the sintering time is 6h~20h.
10. A lithium ion battery comprising a positive electrode, a negative electrode and a separator, characterized in that: The positive electrode comprises the positive electrode material with a coating layer as claimed in any one of claims 1 to 3.
Citation Information
Patent Citations
Modified ternary positive electrode material, preparation method thereof and lithium ion battery
CN116666637A
Ternary positive electrode material for lithium ion battery and preparation method of ternary positive electrode material
CN116741980A
Coated modified positive electrode material and preparation method thereof, positive electrode plate, secondary battery and electric device
CN117790740A
Positive electrode material, preparation method thereof, positive electrode plate and electrochemical device
CN118738368A
Positive electrode material, lithium ion battery and preparation method
CN119361656A
Cited By
Lithium-rich manganese-based positive electrode material and preparation method and application thereof
CN121134853A